Discussion of the importance of ultrasound for the preoperative diagnosis of ovarian tumors (the main provisions of the consensus of leading international organizations, published in June 2021) - M. A. Chekalova; A. G. Kedrova; E. Yu. Cherkasov; V. S. Kryazheva; T. A. Greyan (ABV-press, 2024)
The aim of this work is to analyze the main provisions of consensus, leading international organizations to identify significant ultrasound signs of ovarian tumors at the stage of preoperative diagnosis. Considering the fact that malignant ovarian tumors do not always have specific signs and are accessible to imaging methods, therefore, the risk stratification model in the system of reports and data on ovaries and appendages (O-RADS) is a useful tool that helps classify the formation of appendages into higher risk categories.